PROVISION OF SURFACE VEHICLE STEERABILITY BY REGULATION OF WHEEL TRACTIVE FORCES - D. A. Doubovik (Наука и техника)
Method for regulation of wheel tractive forces for providing better surface vehicle steerability has been developed. Results of investigations in respect of realization of the proposed method with an example of regulation of wheel tractive forces of a vehicle having a wheel formula 88 with two forward steering axles and mass-geometrical parameters which are close to the parameters of the MZKT-79091 off-road vehicle while modeling the «lane change» maneuver are given in the paper.